The reducing value of the evidential particles "pel que sembla" and "segons (que) sembla" in contemporary Catalan - Rossowova, Lucie (Romanica Olomucensia, 2020)
The paper attempts to explore the issue of the Catalan evidentials "pel que sembla" and "segons (que) sembla" and examines their possible pragmatic functions of reducing in speech. It intends to find answers related to the pragmatic orientation of the reducing of the forms under study, with their frequency in spoken and written use and with the relationship between the reducing and the reported or inference evidentness. The analysis studies samples from different genres, on the basis of which the intention is to find out which is the reducing mission of these particles. On the one hand, we use spoken conversations, formal as well as informal, and, on the other hand, speech acts found in newspaper texts and in literary texts are used. Obviously, all the examples that are analysed carry the fundamental meaning which refers to the source of the information which is communicated. In the contexts where there is some potential threat to the personal image of the speakers, the evidential character of the discourse particles under study reduces the speaker's responsibility concerning the content of the message and this use relates to the phenomenon of the linguistic reduction. The use of the particles under study is primarily productive in the written language and, besides, it seems particularly fruitful in scientific and newspaper texts. On the basis of the results of this work it can be noted that the reported uses, as well as the inference uses, in obedience to the context, can be associated with the reducing function of the evidential particles.
Keywords: evidentiality; reducing; pel que sembla; segons (que) sembla; politeness